Perancangan Sistem Informasi Pembayaran Uang Sekolah Berbasis Web - Erihot Medi Saputra Tarigan; Furqan Khalidy; Saiful Amur; Mardiah Mardiah (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
The problem in managing payment of the Educational Development Contribution (SPP) at SMA Negeri 19 Medan lies in the system that relies on manual recording and payment cards. This creates obstacles such as delays in generating financial reports and difficulties monitoring students' late payments. To address this issue, implementing a computerized SPP payment information system is essential. The objective of this research is to accelerate financial reporting in real-time, facilitate monitoring of student payments, and provide parents with access to monitor payment statuses and receive late payment notifications. The research method employs the System Development Life Cycle (SDLC) as the primary framework for designing and developing the SPP payment information system. The stages include planning, analysis, design, implementation, testing, and integration, as well as maintenance. Data sources were obtained through interviews with various school stakeholders, including the school treasurer, principal, and several students. The purpose of the interviews was to identify existing problems and understand the mechanisms of SPP management. Data management was conducted using MySQL, specifically through CRUD operations (Create, Read, Update, and Delete) and MySQL queries. This approach simplifies the addition and monitoring of data. The research findings indicate that implementing this web-based information system provides an effective solution to the problems in managing the school payment system at SMA Negeri 19 Medan.